Evaluasi Pembelajaran Menulis di Kelas Tinggi - Juni Sahla Nasution; Adelina Br Sembiring; Dinda Patliana Sukma; Siti Fifi Juliani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Writing is the ability to use language to communicate using written words, is the process of obtaining or expressing graphic symbols in language that other people can understand, and is the process of obtaining or expressing graphic symbols in language that other people can read. People who take part in this activity are called writers. The results of the activities will be stated in written form. This means that other people will read it so that the ideas conveyed by the author can be accepted by readers. This type of research is library research. Evaluation is carried out through analysis or presentation of literature, for example academic journals, as the main source of information. Therefore, writing assessment is an activity that measures or evaluates students' writing skills. This is done to find out how well students have achieved the writing learning objectives that have been set.